IMPLEMENTATION OF FINANCIAL MANAGEMENT POLICIES IN THE PROVINCIAL HEALTH OFFICE OF CENTRAL SULAWESI - Wiwinarsih, Wiwinarsih; Riadi, Slamet; Kurnia, Intam; Irfan Mufti, Mohammad (CV. Lafadz Jaya, 2024)
This research aims to analyze and explain the implementation of financial management policies at the Provincial Health Office of Central Sulawesi. The research method is qualitative descriptive, and data collection techniques include observation, interviews, and documentation. This research was conducted at the Provincial Health Office of Central Sulawesi using a purposive sampling technique with five informants. Based on the results and discussion, according to Government Regulation No. 12 of 2019 regarding regional financial management, which includes planning and budgeting, implementation, administration, and accountability, it shows that communication has been effective, conducted through technical guidance, meetings, and information dissemination. The quantity of human resources is adequate, but their quality is still lacking in competence. The disposition has been functioning well, characterized by support and commitment from policy implementers. However, the bureaucratic structure has not been optimal. In conclusion, the implementation of financial management policies at the Provincial Health Office of Central Sulawesi has not yet been fully effective.